PERSEPSI MAHASISWA PROGRAM S-1 PENDIDIKAN TEKNIK BANGUNAN TERHADAP BIMBINGAN GURU PAMONG PADA KEGIATAN PPLK UNIVERSITAS NEGERI PADANG SEMESTER JULI-DESEMBER TAHUN 2016 - 2141-2145, Nafil Sabok Tono (Universitas Negeri Padang, 2018)
Abstract— This research begins from the reality that there are many students who lack guidance from pamong teachers while PPLK . Even let students teach in the classroom without being mentored first. This is due to many factors such as lack of communication between PPLK student and pamong teacher, and the appointment of pamong teachers who do not appropriate procedures. This rsearch is to reveal the student perceptions of S-1 PTB on the guidance of pamong teachers in PPLK activities among semester July to December 2016. This type of research is descriptive-quantitative research with population of all students PPLK semester July-December 2016 Prodi S-1 PTB UNP which are 72 people. The sample is 72 students using total sampling technique. Data analysis technique used is using formula percentage F / N x 100%, then result of processed data percentage seen in category percentage of achievement. The results of this study is shows the perception between of PPLK students of S-1 PTB UNP to the guidance of teachers pamong is enough. In accordance with the percentage of achievement obtained is 78%. The percentage between teaching and non teaching activity achievement was also 78%. And then, most of the PPLK students of S-1 program of PTB UNP semester of July-December 2016 has more positve perception about pamong teachers. Keywords: Student Perception, PPLK, Guidance, Pamong Teacher